Drying the waste generated by pressing apples using solar energy - Urayimjonov Asrorjon Ahadjon oʻgʻli.; Axmedov Solmonxon Alisher oʻgʻli.; Abdullayev Dilmurodjon Dilshodjon oʻgʻli (Zien Journals, 2023)
The Juice developed from unripe raw materials contains a large amount of acid, low in sugar, it is sour. Apples are sent either to production or storage, depending on the quality, degree of ripeness. Depending on the degree of ripening of apples, a plan table is drawn up for storing raw materials, and according to this table, apples are ready for processing
Keywords: apple; pressing; energy; generated